Purine metabolism in plant pathogenic fungi - Sun, Manli; Dai, Pengbo; Cao, Zhiyan; Dong, Jingao (Frontiers in Microbiology, 2024)
In eukaryotic cells, purine metabolism is the way to the production of deoxyribonucleic acid (DNA) and ribonucleic acid (RNA) and plays key roles in various biological processes. Purine metabolism mainly consists of de novo, salvage, and catabolic pathways, and some components of these pathways have been characterized in some plant pathogenic fungi, such as the rice blast fungus Magnaporthe oryzae and wheat head blight fungus Fusarium graminearum. The enzymatic steps of the de novo pathway are well-conserved in plant pathogenic fungi and play crucial roles in fungal growth and development. Blocking this pathway inhibits the formation of penetration structures and invasive growth, making it essential for plant infection by pathogenic fungi. The salvage pathway is likely indispensable but requires exogenous purines, implying that purine transporters are functional in these fungi. The catabolic pathway balances purine nucleotides and may have a conserved stage-specific role in pathogenic fungi. The significant difference of the catabolic pathway in planta and in vitro lead us to further explore and identify the key genes specifically regulating pathogenicity in purine metabolic pathway. In this review, we summarized recent advances in the studies of purine metabolism, focusing on the regulation of pathogenesis and growth in plant pathogenic fungi.